Severe late onset capillary leak syndrome post allo-HSCT successfully treated by bevacizumab: a case report - Song Xue; Jiaqi Chen; Yuzhu Shi; Lina Zhang; Man Chen; Huipeng Sun; Xingyu Cao; Fang Wu (Frontiers in Medicine)
This article describes a case of successful management of late-onset CLS occurring after allo-HSCT, employing bevacizumab as the therapeutic agent. Capillary leak syndrome (CLS) represents a critical complication arising from allogeneic hematopoietic stem cell transplantation (allo-HSCT). The prognosis for CLS remains considerably constrained. A targeted therapeutic approach targeting vascular endothelial growth factor (VEGF) offers a novel strategy for the management of CLS.